Eletrodeposição de Ag em meio de líquido iônico prótico - Sousa, Natalia Gomes (2021)
The electrodeposition of silver is essential for industry and commerce, through the manufacture of aesthetic products or electronic devices, being regularly carried out in alkaline cyanide baths that are highly corrosive and toxic. This work presents a methodology using protic ionic liquid (PIL), 1-H methylimidazolium hydrogen sulfate [HMIM+ ] [HSO4 − ] as a support electrolyte in the electrodeposition of silver on gold electrode, as an environmentally friendly alternative to a process. Cyclic voltammograms for the redox pair Ag+ / Ag revealed the presence of a process for reduction and oxidation of Ag+ ions, without potential 0,06 ± 0,006 V, being an almost reversible process. The effect of temperature on the electrodeposition of silver is known to be limited to a temperature above 35 ºC, due to the balance between the Ag+ cations and the HSO4 − anion in the PIL. Using the Cottrell equation, the diffusion coefficient (D) values of Ag+ ions were calculated in [HMIM+ ] [HSO4 − ] at 23.5; 35 and 45 ºC. The D values were 6.67 × 10−8 ; 6.94 × 10−8 and 4.32 × 10−8 cm2 s −1 , respectively. The dependence on the diffusion coefficient values related to the equilibrium hypothesis, which was confirmed by the Density Functional Theory. The result of this thermodynamic calculation proved to be exergonic. The morphology of the silver electrodeposits has changed as to the deposition mode (potentiostatic and galvanostatic), the shape of the dendrites has changed. The electrodeposit with the highest uniformity was obtained galvanostatically at 45 °C.